PENGARUHÂ STRATEGI KELOMPOK PENGENANGAN INDAH(REMINISCENCE Â GROUP STRATEGIES)TERHADAP PENURUNAN TINGKAT DEPRESI PADALANJUT USIA DI PANTI WREDHAMOJOPAHIT MOJOKERTO - Nur Hidayati, Rina; Ibnu, Faisal (Jurnal Keperawatan Bina Sehat, 2009)
Aging is prosess looses network capability of repairmen his self or changing his self to defend the structure and function normally. At this step, the individual gets more changing physically, mentally and physic social. Stress of environment and lost his capability takes adaptation of environment changing because of elderly’s depression. The problem of this research is whether the effect of Reminiscence group strategy decrease of the level of elderly’s depression in Mojopahit Folk’s Home Mojokerto.The design of this research is pra experimwnt one group pretest – pretest. Remeniscence group strategy is independent and dependent variable is depression of elderly. Sample of this reseacrh is twenty persons that devided by two rollers and giving good servant together. The lvel of depression is Reminiscence group strategy of the level of elderly”s depression is examined by Wilcoxon signed by Rank Test using SPSS 16. 0 for windos.The work of this research shows the effect of Reminiscence group strategy of decrease level depresion in Mojokerto folk’s home mojokerto that is shown by p = 0,000 (p<α0,05). It can be caused by raising satisfaction of elderly, until he can dicharges his depression.The reminiscense Group Strategy should be in Mojopahit Folk’s Home Mojokerto to discharge depression feeling of elderly. And it is needed by seeking more good good topic enjoyable and the writer hopes that Reminiscence Group Strategy is the most useful in discharging of the level of elderly’s depression.Keyword : elderly, depression, Reminiscence Group Startegy.